"Green'' Particle Technology? - Peukert, Wolfgang; Bück, Andreas (2022)
In this essay, we discuss the evolution of particle technology in the context of climate change. We begin with a brief outline of the history of particle technology. In addition to the fascination of fine particle systems, it will become clear that particles have also been associated with negative consequences of human activities since the industrial revolution and still are. Some examples of how dispersive systems contribute to solving current challenges are discussed. Finally, we identify white fields and open questions in particle engineering in the context of climate change hoping that this will stimulate further research.
Keywords: Particles; Particle technology; Sustainability